Epicardial adipose tissue related to left atrial and ventricular function in heart failure with preserved versus reduced and mildly reduced ejection fraction. (26th June 2022) - Jin, Xuanyi; Hung, Chung‐Lieh; Tay, Wan Ting; Soon, Dinna; Sim, David; Sung, Kuo‐Tzu; Loh, Seet Yoong; Lee, Sheldonn; Jaufeerally, Fazlur; Ling, Lieng Hsi; Richards, A Mark; van Melle, Joost P.; et al.
Abstract : Aim: Different associations between epicardial adipose tissue (EAT) and cardiac function have been suggested in patients with heart failure with preserved (HFpEF) versus reduced and mildly reduced ejection fraction (HFrEF/HFmrEF). However, few studies have directly compared the association between EAT and left atrial (LA) and left ventricular (LV) function in patients with HFpEF and HFrEF/HFmrEF. Methods and results: We studied EAT thickness using transthoracic echocardiography in a multicentre cohort of 149 community‐dwelling controls without heart failure, 99 patients with HFpEF, and 366 patients with HFrEF/HFmrEF. EAT thickness was averaged from parasternal long‐axis and short‐axis views, respectively, and off‐line speckle tracking analysis was performed to quantify LA and LV function. Data were validated in an independent cohort of 626 controls, 243 patients with HFpEF, and 180 patients with HFrEF/HFmrEF. For LV function, LV global longitudinal strain (GLS) was measured in both derivation and validation cohorts. For LA function, LAGLS at reservoir, contractile and conduit phase were measured in the derivation cohort, and only LAGLS at reservoir phase was measured in the validation cohort. In the derivation cohort, EAT thickness was lower in HFrEF/HFmrEF (7.3 ± 2.5 mm) compared to HFpEF (8.3 ± 2.6 mm, p  < 0.05) and controls (7.9 ± 1.8 mm, p  < 0.05). Greater EAT thickness was associated with better LV and contractile LA function in HFrEF/HFmrEF, but not in HFpEF ( p for interaction <0.05). These findings were confirmed in the validation cohort, where EAT thickness was lower in HFrEF/HFmrEF (6.7 ± 1.4 mm) compared to HFpEF (9.6 ± 2.8 mm; p  < 0.05) and controls (7.7 ± 2.3 mm; p  < 0.05). Greater EAT thickness was associated with better LV and reservoir LA function in patients with HFrEF/HFmrEF but worse LV and reservoir LA function in patients with HFpEF ( p for interaction <0.05). Thickened EAT (EAT thickness >10 mm) was associated with LA dysfunction (LAGLS at reservoir phase <23%) in HFpEF, but not in HFrEF/HFmrEF. Conclusion: Epicardial adipose tissue thickness is greater in patients with HFpEF than HFrEF/HFmrEF. Increased EAT thickness is associated with worse LA and LV function in HFpEF but the opposite in HFrEF/HFmrEF.